Time to recovery from severe pneumonia and its predictors among children aged 2–59 months admitted to the Asella Referral and Teaching Hospital, Asella, Ethiopia, 2023: a retrospective cohort study - Tewodros Mekonin Bayu; Assefa Legesse Sisay; Ayantu Kebede (BMJ Open)
Objective To determine the time to recovery from severe pneumonia and its predictors in children aged 2–59 months admitted to the Asella Referral and Teaching Hospital, Ethiopia.Design, participants, and setting An institution-based retrospective cohort study was conducted on 424 children aged 2–59 months in Asella Town, Ethiopia. Medical records of eligible children were selected using a simple random sampling technique. The Kaplan-Meier curve and log-rank test were used to describe the survival function. Independent predictors of recovery time were identified using Cox regression analysis. The 95% CI of the HR with a corresponding p value of 0.05 was used to declare statistical significance.Primary and secondary outcomes Recovery time from severe pneumonia and its predictors.Results The median recovery time was 5 days. The incidence density of recovery was 16 (95% CI: 14.44 to 17.76) per 100-person-day observation. Being a rural resident (adjusted HR (AHR): 0.68; 95% CI: 0.57 to 0.82), aged 36–59 months (AHR: 0.70; 95% CI: 0.50 to 0.98), being underweight (AHR: 0.75; 95% CI: 0.59 to 0.95), the presence of danger signs (AHR: 0.31; 95% CI: 0.24 to 0.39) and having comorbidity (AHR: 0.38; 95% CI: 0.30 to 0.48) were significant predictors of time to recovery in children aged 2–59 months.Conclusion In this study, the median recovery time was longer than that reported in similar studies. Age, residence, underweight, danger signs and comorbidities were significant predictors. Therefore, families of children with identified predictors need counselling to prepare for the likelihood of slow recovery.